Output and Unemployment Dynamics during the Great Recession : A Panel Unobserved Components Analysis - Vitek, Francis (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes the sources of output and unemployment dynamics in the world economy during the Great Recession. This analysis is based on a panel unobserved components model of the world economy, disaggregated into its fifteen largest national economies. We find that excess supply pressure was primarily transmitted from the output market to the labor market by economy specific combinations of negative domestic or foreign output demand shocks, mitigated to varying degrees by countercyclical labor market policies or institutions.